DAYA SAING DAN KINERJA EKSPOR KOMODITAS UDANG BEKU INDONESIA TERHADAP NEGARA KOMPETITOR UTAMA DI JEPANG - Sri Rahayu (Politeknik Bisnis Indonesia, 2023)
Shrimp is the fisheries and fishery product commodity with the largest overall export value in Indonesia. Fresh shrimp, frozen shrimp, and processed shrimp are the three categories of Indonesian shrimp exports. When compared to other varieties of shrimp, frozen shrimp has the highest export value. Japan is a major market for Indonesian frozen shrimp exports. However, the value of Indonesian frozen shrimp exports to Japan had a declining pattern of volatility between 2012 and 2021. The situation of export values fluctuating in a negative trend may suggest the probability of difficulties with commodity export competitiveness and performance. The goal of this study is to compare the competitiveness and export performance of Indonesia's frozen shrimp commodity to the biggest rival in Japan. This study employed the Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) methods. The findings demonstrated that Indonesia's frozen shrimp commodity is competitive with Japan's top rival. Meanwhile, Indonesian frozen shrimp goods' export performance in Japan remains inadequate.